2019
DOI: 10.1186/s12885-019-5276-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the BACH2 and PRDM1 genes in lymphocytes from healthy donors and chronic lymphocytic leukemia patients

Abstract: BackgroundAge-related genetic changes in lymphocyte subsets are not currently well documented. BACH2 is a transcription factor that plays an important role in immune-mediated homeostasis by tightly regulating PRDM1 expression in both B-cells and T-cells. BACH2 gene expression is highly sensitive to DNA damage in aged mice. This concept led us to investigate the variation in BACH2 and also PRDM1 expression in major lymphocyte subsets with age.MethodsLymphocyte subsets from 60 healthy donors, aged from 20 to 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…[29] Moreover, Bach2 has been reported to affect immunosenescence since its expression was negatively associated with age in human immune cells. [30] Our study also suggested that Bach2 mRNA was decreased in elders with the highest AUC value, which supports the previous results.…”
Section: Discussionsupporting
confidence: 91%
“…[29] Moreover, Bach2 has been reported to affect immunosenescence since its expression was negatively associated with age in human immune cells. [30] Our study also suggested that Bach2 mRNA was decreased in elders with the highest AUC value, which supports the previous results.…”
Section: Discussionsupporting
confidence: 91%
“…PRDM1 and REST were reported to be functionally associated with aging. For instance, PRDM1 in the brown module from Asian (Chinese) was found to be significantly correlated with age in human immune cells and might be involved in immunosenescence ( Chi et al, 2019 ). REST had been reported regulated the human brain aging ( Lu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have characterized the role of BACH2 in a number of immune cell types [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, changes in CTL killing have not been examined.…”
Section: Discussionmentioning
confidence: 99%